2011
DOI: 10.1111/j.1600-6143.2011.03774.x
|View full text |Cite
|
Sign up to set email alerts
|

What’s New, What’s Hot in Solid Organ Transplantation? Summary of the American Transplant Congress 2011

Abstract: Breakthroughs in basic and clinical science in solid organ transplantation were presented at the American Transplant Congress 2011. Key areas of presentation included the pathogenesis of late allograft failure, immune regulation and tolerance, pathways in allograft injury, electing appropriate patients for transplantation, determining the best allocation schemes to maximize effective utilization, organ preservation, monitoring the alloimmune response and immunosuppressive management. In this review, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They found that although treatment with either IL-2C or G-CSF led to a significant delay of MHC-II disparate allogeneic donor skin rejection, the combinatorial treatment was superior to either alone, confirming that MDSCs and Treg prolonged skin allograft survival in mice. Karp and Mannon [51] summarized identified an HLA-Dq α -class-II-derived peptide that was a potent inducer of CD11b+CD115+Gr1+ MDSCs. Moreover, this peptide prolonged the survival of fully mismatched mouse cardiac allografts associated with the induction of Foxp3+ Treg.…”
Section: Suppressive Function Of Mdscsmentioning
confidence: 99%
“…They found that although treatment with either IL-2C or G-CSF led to a significant delay of MHC-II disparate allogeneic donor skin rejection, the combinatorial treatment was superior to either alone, confirming that MDSCs and Treg prolonged skin allograft survival in mice. Karp and Mannon [51] summarized identified an HLA-Dq α -class-II-derived peptide that was a potent inducer of CD11b+CD115+Gr1+ MDSCs. Moreover, this peptide prolonged the survival of fully mismatched mouse cardiac allografts associated with the induction of Foxp3+ Treg.…”
Section: Suppressive Function Of Mdscsmentioning
confidence: 99%